THE USE OF GOOGLE SITES AS A LEARNING MEDIUM TO IMPROVE STUDENTS’ COGNITIVE LEARNING OUTCOMES AND SELF-EFFICACY IN THE TOPIC OF BASIC LAWS OF CHEMISTRY - Azizah, Putri Augista Nur; Sulistina, Oktavia; Setyowati, Istri (Universitas Negeri Surabaya, 2025)
This study aims to determine the improvement in students’ cognitive learning outcomes and self-efficacy through the use of Google Sites as a learning medium. The study was conducted at SMA Laboratorium UM in class X.4 in the 2024/2025 academic year with 36 students. The study was conducted using a Classroom Action Research (CAR) method. The instruments used were observation sheets, test questions, and self-efficacy questionnaires. The study results showed that the implementation of learning in cycle I was 88.28% and in cycle II was 90.50%. In addition, students’ cognitive learning outcomes increased, as evidenced by the students’ classical completeness rate, which rose from 44.44% in cycle I to 88.89% in cycle II. Students’ self-efficacy also increased from 24.50 to 30.14 in cycle II and was categorised as high. Thus, the use of Google Sites as a learning medium has been shown to improve students’ cognitive learning outcomes and self-efficacy in the context of the Basic Laws of Chemistry material.